Modern Intensive Care Unit Design : A Literature Review - Wijaya, Andryadi; Jufan, Akhmad Yun; Adiyanto, Bowo (The International Journal of Medical Science and Health Research, 2024)
The need for Intensive Care Units (ICUs) continues to increase over time. In Canada, 11% of hospitalized patients are referred to the ICU, while in the United States, up to half of the population receives ICU care in their last year of life. Standardization of ICU design and operations is considered essential for efficiency and high-quality patient care. The ICU is a clinical care unit to monitor and support the vital functions of potentially life-threatening critical patients. The organization and management of critical care services are key components that contribute to ICU performance and can impact patient outcomes and healthcare costs. Modern ICU design should consider various elements such as layout, isolation rooms, staff areas, and family rooms. Technological developments such as Smart ICU and the ICU Without Walls concept demonstrate innovation in efficiency improvement and patient safety. The continuity of care activities in the ICU requires skilled human resources, adequate facilities, effective management, and a deep understanding of good ICU design. Technology integration and multidisciplinary approaches are essential to optimize critical patient care and improve clinical outcomes.